Lignans From Forsythia x Intermedia Leaves and Flowers Attenuate the Pro-inflammatory Function of Leukocytes and Their Interaction With Endothelial Cells - Michalak, Barbara; Filipek, Agnieszka; Chomicki, Piotr; Pyza, Małgorzata; Woźniak, Marta; Żyżyńska-Granica, Barbara; Piwowarski, Jakub P.; Kicel, Agnieszka; Olszewska, Monika A.; Kiss, Anna K. (Frontiers in Pharmacology, 2018)
Aim of the study: Taking into account that overactivated leukocytes are an important factor in the development of many chronic diseases, we investigated the activity of phytochemically characterized (HPLC-DAD-MSn) extracts from forsythia leaves and flowers on the pro- and anti-inflammatory functions of leukocytes (effects on IL-1β, IL-8, TNF-α and TGFβ release) and their adherence to endothelial cells. Using bio-guided fractionation, we isolated the active compounds and determined their biological activity, and we included the positive control quercetin. Methods: The effect on IL-1β, TNF-α, IL-8 and TGF-α production by leukocytes was measured by enzyme-linked immunosorbent assay (ELISA). The surface expression of adhesion molecules was analyzed with flow cytometry, and the neutrophil attachment to the endothelial cells was assessed fluorimetrically. The effects on p38MAPK, ERK1/2 and JNK phosphorylation were determined using western blots. Results: Leaf extracts had the effect of decreasing TNF-α production in neutrophils and monocyte/macrophage cells. The bio-guided fractionation led to the isolation of the following lignan aglycones: (+)-pinoresinol, (+)-epipinoresinol, (-)-matairesinol, (+)-phillygenin and (-)-arctigenin. Only phillygenin was able to stimulate the anti-inflammatory function of macrophages by inducing TGF-β release and IL-10 receptor surface expression. Arctigenin, phillygenin and a metabolite produced by the gut microbiota, enterolactone, decreased TNF-α and IL-1β production and neutrophil adhesion to endothelial cells, probably by attenuating the p38 and ERK kinase pathways. Conclusion: Forsythia x intermedia is a valuable source of active lignans, which may be potential candidates for treating inflammatory diseases that are associated with the excessive production of cytokines such as TNF-α and IL-1β.